Influence of rivaroxaban compared to vitamin K antagonist treatment upon development of cardiovascular calcification in patients with atrial fibrillation and/or pulmonary embolism. Issue 4 (25th March 2022) - Stöhr, Robert; Dirrichs, Timm; Kneizeh, Kinan; Reinartz, Sebastian; Frank, Dario; Brachmann, Johannes; Schroeder, Joerg; Schurgers, Leon; Göttsch, Claudia; Keszei, Andras; Floege, Jürgen; Marx, Nikolaus; et al.
Abstract: Background: Vitamin K antagonists (VKA) such as warfarin or phenprocoumon have been the mainstay of therapy for long‐term oral anticoagulant therapy (OAT) in patients with atrial fibrillation or with pulmonary embolism. Due to interferences with matrix Gla‐protein, an important vitamin K‐dependent local calcification inhibitor in cardiovascular structures, VKA antagonists stimulate cardiovascular calcification (CVC). In contrast, rivaroxaban, a nonvitamin K‐dependent oral anticoagulant (NOAC), should be neutral in terms of CVC. We seek to investigate these potential differences in CVC development between VKA versus NOACs in a randomized controlled trial (RCT). Methods: The influence of rivaroxaban compared to vitamin K antagonist treatment upon development of cardiovascular calcification in patients with atrial fibrillation and/or pulmonary embolism trial (NCT02066662) is a multicenter, prospective RCT with a two‐arm, open‐label study design. The primary endpoint is the progression of coronary and aortic valve calcification (quantified as calcification volume score) as assessed by cardiac computed tomography (CT) at 24 months in patients either treated by rivaroxaban or VKA. A total of 192 patients were randomized in a 1:1 fashion. The main inclusion criteria were the presence of atrial fibrillation and/or pulmonary embolism with the indication for OAT and pre‐existent coronary calcification. The development of CVC will be assessed by follow‐up CT at 12 and 24 months. Results: In total 192 patients (median age 70, 72% male) were enrolled over a period of 5 years and followed up for 2 years.